Barriers and Challenges of Building Information Modelling Implementation in Jordanian Construction Industry - Al-Btoush, Mohammed A. KA.; Ahmad Tarmizi, Haron (GJESRM, 2017)
Construction companies are faced with the need to innovatively integrate the construction process and address project development challenges. One way of doing that is the integration of building information modelling (BIM) in the building design and development cycles. However, due to the lack of clear understanding and the absence of a holistic implementation guideline, many companies are unable to fully achieve BIM potentials or implement BIM in their project and building lifecycle. BIM implementation is increasingly challenging in the Jordanian construction industry. Research demonstrates that successful BIM implementation is possible through the identification of the barriers and challenges, which is a basic precondition for the transition of BIM in In the Jordanian construction industry. This study analyzes the barriers, challenges, and the maturity levels of BIM adoption in Jordan construction industry to develop a BIM implementation framework for better understanding of BIM. Thus, enables the industry towards more extensive BIM implementation. The researcher demonstrated this framework by analyzing survey responses to measure the challenges, barriers, and maturity of BIM’s implementation and discuss the framework’s utility for the Jordanian building industry.